2009
DOI: 10.1126/science.1166112
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Mechanism for Microsaccade Generation in the Primate Superior Colliculus

Abstract: During fixation, the eyes are not still, but often exhibit microsaccadic movements. The function of microsaccades is controversial, largely because the neural mechanisms responsible for their generation are unknown. Here we show that the superior colliculus (SC), a retinotopically organized structure involved in voluntary-saccade target selection, plays a causal role in microsaccade generation. Neurons in the foveal portion of the SC increase their activity before and during microsaccades with sizes of only a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
475
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(513 citation statements)
references
References 28 publications
36
475
2
Order By: Relevance
“…This is larger than in most studies, although there is also considerable variability between the average microsaccade amplitudes described in past reports, which include 0.8° (Bair and O'Keefe, 1998) (Ko et al, 2010;Poletti and Rucci, 2010), and 0.23° ( Hafed et al, 2009).…”
Section: Resultscontrasting
confidence: 38%
See 2 more Smart Citations
“…This is larger than in most studies, although there is also considerable variability between the average microsaccade amplitudes described in past reports, which include 0.8° (Bair and O'Keefe, 1998) (Ko et al, 2010;Poletti and Rucci, 2010), and 0.23° ( Hafed et al, 2009).…”
Section: Resultscontrasting
confidence: 38%
“…Moreover, the activity of microsaccade-selective neurons during macrosaccades was similar to the activity of macrosaccade-selective neurons during microsaccades, indicating a continuous representation of amplitude in the cerebellum. These results dovetail nicely with recent work showing that muscimol injection to the fastigial oculomotor region, the output structure of the oculomotor vermis (Yamada and Noda, 1987;Noda et al, 1990), biases the endpoints of both microsaccades and macrosaccades to ipsilesional space (Goffart et al, 2004;Guerrasio et al, 2010) and a growing body of research suggesting that the functions of the oculomotor control system are similar for microsaccades and macrosaccades (Van Gisbergen et al, 1981;Brien et al, 2009;Hafed et al, 2009;Ko et al, 2010;Hafed, 2011;Hafed and Krauzlis, 2012;Van Horn and Cullen, 2012;Poletti et al, 2013). We conclude that the cerebellum's role in the control of saccades extends even to the oculomotor system's smallest saccades, which occur during fixation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No studies to date have conducted recordings from inhibitory burst neurons in connection with microsaccades, however (31). Omnipause neurons in the raphe stop firing during both saccades and microsaccades (32,33), and population activity in the superior colliculus map generates microsaccades and saccades in equivalent fashion (9,34). The hypothesis of a fixation-exploration continuum reconciles the dynamics of oculomotor behavior with the proposal of a common microsaccade-saccade generator (9-11), and it moreover elucidates previously unexplained results concerning the precise relationship between saccades and microsaccades, such as the finding that subjects can make voluntary saccades that are as small as fixational microsaccades (12).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the task may have modulated subjects' fixational eye movements. SC contains neurons responsive to microsaccades near the foveal (rostral) regions (Hafed et al, 2009), and recent evidence has suggested a link between microsaccades and covert attention (Engbert and Kliegl, 2003;Hafed et al, 2009). However, in our experiment the observed responses were in more central regions of SC that correspond to the peripheral visual field, reducing the likelihood that the responses were generated by microsaccade-related activity.…”
Section: Discussionmentioning
confidence: 99%